Mathematic Literation Abilities Based on PISA-Like - Baroroh, Ummu; Tririnika, Yuliana; Yuliani, Ida (Universitas Sebelas Maret, 2019)
Literacy is one of the abilities should be owned by students in prepare competitiveness due to the development of the knowledge and technology in the 21st century. Literacy is a student ability to formulate, application, and interpreted mathematics in various contexts. Mathematics literacy is the one of abilities assessed in the PISA study. The purpose of this research is to determine how the literacy skills of student at SMP 24 Surakarta. The research conducted by descriptive quantitative to seeing the literacy abilities of student. The research was conducted by subtract sample 3 student of IX class and from the result of the test it was found that the literacy skills of student were low. Low literacy skills are due to the inaccuracy of student and a lack of understanding of concept in working on these problems.